Maternal Age at Marriage and Risk of Childhood Stunting: Evidence from a Case-Control Study in North Sumatra, Indonesia (Gema Lingkungan Kesehatan, 2025)
Stunting remains a major public health issue in Indonesia, particularly in urban areas such as Medan. While socioeconomic and nutritional factors are well recognized, the influence of maternal age at marriage on child growth is less explored. This study examined the association between maternal age at marriage and childhood stunting in Medan, Indonesia. Methods. An analytical observational study with a case–control design was conducted from January to March 2025 across several community health centres in Medan. A total of 124 mother–child pairs (62 stunted and 62 non-stunted children) were selected using cluster random sampling. Data were collected through structured interviews and health-record reviews. Stunting was defined as height-for-age Z-score < -2 SD based on WHO standards. Logistic regression was used to assess the relationship between maternal age at marriage (